2004
DOI: 10.1002/ajp.20018
|View full text |Cite
|
Sign up to set email alerts
|

Scalp EEG for the diagnosis of epilepsy and photosensitivity in the baboon

Abstract: Spontaneous seizures have been observed in several baboon species housed at the Southwest National Primate Research Center (SNPRC), including Papio hamadryas anubis and cynocephalus/anubis, hamadryas/anubis, and papio/anubis hybrids. The goal of this study was to establish a noninvasive, reliable electroencephalographic technique to characterize epilepsy phenotypes and assess photosensitivity in these subspecies. Thirty baboons with witnessed seizures, and 15 asymptomatic baboons underwent scalp electroencepha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
(16 reference statements)
1
8
0
Order By: Relevance
“…A previous scalp EEG studies in a smaller group of animals selected from this pedigree, demonstrated that the natural epilepsy of the baboon model closely resembles one of the most common epilepsy syndromes in humans, juvenile myoclonic epilepsy (JME; Szabó et al, 2004, 2005). The seizures are generalized myoclonic or tonic–clonic in character, present chiefly in adolescence, occur predominantly in the morning and can be provoked by stress, handling and ketamine administration.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…A previous scalp EEG studies in a smaller group of animals selected from this pedigree, demonstrated that the natural epilepsy of the baboon model closely resembles one of the most common epilepsy syndromes in humans, juvenile myoclonic epilepsy (JME; Szabó et al, 2004, 2005). The seizures are generalized myoclonic or tonic–clonic in character, present chiefly in adolescence, occur predominantly in the morning and can be provoked by stress, handling and ketamine administration.…”
Section: Introductionmentioning
confidence: 85%
“…The methods for the scalp EEG studies were described by our group previously (Szabó et al, 2004, 2005). The surface electrodes are placed according to the standard international 10–20 electrode placement system at FP1, FP2, T8, C4, Cz, C3, T7, O1, O2, A1 and A2 positions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of the EEG studies lasted for about one hour, and included repeated trials of ILS. The baboons were sedated with ketamine, which at low doses, similar to humans with a predisposition to epilepsy, can activate IEDs [10, 11] without suppressing the photoparoxysmal response [12]. …”
Section: Introductionmentioning
confidence: 99%